2019
DOI: 10.1016/j.sjbs.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacological investigation of Monotheca buxifolia and Bosea amherstiana using animal models

Abstract: Experimental based evidence suggests that most of the medicinal plants possess wide-ranging pharmacological and biological activities that may possibly use in treatment of inflammation-related diseases. The current study was aimed to explore the acute toxicity, analgesic, sedative and antipyretic activities of Monotheca buxifolia and Bosea amherstiana in mices. In vivo experimental models were used in this study. Acute toxicity was evaluated for 24 h’ interval at concentration of 500, 1000, 1500 and 2000 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Infrared spectra (IR) were recorded on Shimadzu IR-460 in nujol or KBr pellets and reported in cm −1 . NMR spectra were recorded on Bruker AMX-500 and AM-400 for 1 H (300–500 MHz) and 13 C (125–150 MHz) spectrometers. "spectra were recorded on Bruker Avance spectrometers ranging from 7.05 up to 14.09 T".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared spectra (IR) were recorded on Shimadzu IR-460 in nujol or KBr pellets and reported in cm −1 . NMR spectra were recorded on Bruker AMX-500 and AM-400 for 1 H (300–500 MHz) and 13 C (125–150 MHz) spectrometers. "spectra were recorded on Bruker Avance spectrometers ranging from 7.05 up to 14.09 T".…”
Section: Methodsmentioning
confidence: 99%
“…is monotypic genus of the family Sapotacea, grows mainly in Malakand Dir district, Pakistan. M. buxifolia is reported for wide-range of pharmacological activities including cough, wound healing, headache, analgesic, antipyretic, antiseptic and urinary tract infections 13 . The antibacterial activity of crude ethanolic extract and fractions of M. buxifolia using agar well diffusion technique confirmed their antibacterial potential 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Fruit of S. mascatense was also found to have some antibacterial properties (Ullah et al, 2017). Methanolic extracts from aerial portions of S. mascatense were found to reduce pain, fever, and inflammation (Hassan et al, 2019). Burki et al (2018) found that extracts of S. mascatense bark had anti-inflammatory and antidepressant properties.…”
Section: Existing and Potential Uses And Benefitsmentioning
confidence: 99%
“…Monotheca buxifolia species founds in hilly areas of Pakistan which has therapeutic uses such as antiseptic, relieving gastrointestinal disorders, analgesic, anti-inflammatory, antipyretic, and wound healings [14]. These plants are found in abundance in Dir Lower, Attock, Xhob Kala Chitta, and Chitral [15].…”
Section: Introductionmentioning
confidence: 99%